(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The researcher tried to show the importance of obligation with the rules of professional conduct set by the Association of Accountants and Auditors of Iraqis when expressing an opinion the financial statements submitted tax administration and enhance the confidence of these lists, and adopted in the tax settling accounts process and its impact on tax revenues, and touched a researcher at the theoretical side of the search to the problem of research and of my Is there a trace of non- not to obligation by the rules of professional conduct in Iraq affect the tax revenue with the rules of professional conduct in tax revenue for companies research sample, the research aims to study the rules of professional conduct set by the Association of Accountants and Auditors of Iraqis and the importance of this commitment for tax administration, and the extent of adoption of the financial statements), and its impact on tax revenues, and adopted researcher basic premise argument ((not to obligation by the rules of professional conduct in Iraq affect the tax revenue))